STRATEGI PR RADIO DAHLIA DALAM MENGHADAPI PERSAINGAN DI ERA INDUTRI 4.0 - Eli Tiara; Femi Oktaviani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The 4.0 industrial revolution requires humans to be able to use and take advantage ofexisting technology. The mass media Radio cannot stand by the conventional model. Radio Dahlia FM Bandung is a private radio in the city of Bandung which still exists today and is able to compete amidst tight competitors, this cannot be separated from the role of public relations as a liaison between the company and the public. This study aims to determine the planning of a public relations strategy for Radio Dahlia FM Bandung in facing competition in the industrial era 4.0. The method used is descriptive qualitative with data collection techniques using interviews, observation and documentation. The results of this study Public Relations Radio Dahlia FM Bandung carried out four stages in facing competition in the industrial era 4.0. What has been done by PR includes fact finding, planning, communication and evaluating. Planning for Dahlia radio PR activities, namely by branding activities through the On Air, Off Air program and social media, creating internal events, sponsorship collaboration events and special events, and making dahlia streaming radio innovations, and being more active in social media. In introducing the innovation of streaming radio, dahlia has considered the main elements of innovation diffusion, such as innovation, communication channels, time and social systems.